(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
The adulterant of choice for my sample is sugar cane and corn syrup, which is one of the most frequent adulterants used in a range of honey products. Honey adulteration is a complex issue across the world in general and in our country in particular, according to most studies, and it has a major economic impact. It may be induced by the introduction of various cheap foreign substances. Contamination of honey changes the physiochemical besides rheology of honey, reducing its nutritional and therapeutic qualities. As a result, techniques of adulterate detection and precise measurement of adulterants would have been used to produce high quality honey devoid of any foreign addition. Numerous approaches used for honey adulteration detection by maximum researchers, such as, Liquid Chromatography (LC) and Gas Chromatography (GC) analysis, protein characterization, Near Infra-Red (NIR) spectroscopy, Fourier Transform Infrared (FTIR) spectroscopy with Attenuated Total Reflectance (ATR), High Performance Anion Exchange Chromatography with Pulsed Aerometric Detection (HPAEC-PAD), High Performance Liquid Chromatography Coupled to Isotope Ratio Mass Spectrometry (HPLCIRMS), calorimetric methods, Stable Carbon Isotope Ratio Analysis (SCIRA), Fourier Transform (FT), Raman spectroscopy and microscopic detection techniques are appropriate as well as deliver valuable knowledge. However, to obtain a full besides reliable outcome, people ought not focus just on each technique, but rather use a combination of them.